ENVIRONMENTAL PROTECTION UNDER CONSTITUTIONAL LAW - Škulić, Milan (Glasnik Advokatske komore Vojvodine, 2024)
This paper explains the importance of the protection of the environment under constitutional law. In the context of the protection of the environment under constitutional law, the general ratio legis of the response of criminal law to environmental pollution is analyzed, which, as usual, is based on general constitutional provisions. The paper defines the basic elements of environmental protection rights both in national legal frameworks and from the perspective of the effects of relevant international legal sources, which are applied in accordance with constitutional rules, either through so-called implementation mechanisms or sometimes directly. The paper specifically explains the role of the Constitutional Court in the protection of the environment, illustrated by examples of relevant decisions of this Court, both in the realm of normative control of constitutionality and legality and in proceedings initiated through constitutional appeals.